The protector effect of homologous oncospheres to infection of Hymenolepis nana var. nana - Vásquez, Oriana (2008)
The protector effect of homologous oncospheres was evaluated in Mus musculus infected with Hymenolepis nana var. nana. Twenty female of Mus musculus of two months old, free infection by helminths, were random-selected into two groups, experimental and control, of 10 mouses each one. Each animal from the experimental group received a single subcutaneous dose of immunogen constituted by 0,05 mL of PBS with 15—24 oncospheres and 0,05 mL of complete Freund’s Adjuvant to induce the immune response. The control group received a similar dose, but without oncospheres. The protector effect of the oncospheres was evaluated after 25 days of the immunization, 200 viable eggs of H. nana var. nana were inoculated by oral route to each one of the 20 mouses, and they were kept alive for 15 days before to be sacrificed to get intestinal parasites and prove the immunization efficiency. Adult forms of H. nana var. nana were found in two mice of experimental group and 5 mouses from control group; being immunization efficiency of 60%, showing significative differences between control group and experimental group.